Effects of Auditory materials in teaching and learning the glorious Quran in junior secondary schools in Yobe state - SHANU, Yunusa Muhammad (CV. Kalimasada Group, 2025)
This research work examined the effects of auditory material in teaching and learning the glorious Qur’an at Ramat in junior secondary school in Yobe state. The study was anchored on constructivist theory. The researcher used both primary and secondary sources from a sample of one hundred (100) respondents obtained by the use of a well-structured questionnaire; the data collected were analyzed using descriptive statistics such as mean. The result that Auditory resources are essential materials in teaching and learning process as their potential for enriching visualizing simplifying, transmitting and accelerating teaching and learning process motivate, both teachers and learners to achieve their aims, it was recommended among other government should provide adequate fund to schools for the purchase of Auditory and other relevant resources for teaching and learning and teachers should improvise instructional materials when need be.